The Educational Value of Islamic Characters in the Film Mengejar Surga (Chasing Heaven) - Ira Fitriyani (al-Afkar, Journal For Islamic Studies, 2024)
The development of media for delivering da'wah is increasingly diverse, not only through direct media but also through films. One of them is a film entitled Chasing Heaven, this film tells the story of a child who searches for his biological father halfway around the world in order to get his blessing and become his guardian at his wedding. This is interesting because the child is willing to look for his father in other parts of the country and overcome many difficult obstacles so that he can teach the valuable value of struggle. The process of understanding the message of preaching in the film Mengjar Surga uses Roland Barthes' semiotic analysis. The aim of this research is to determine the values of Islamic character education based on Roland Barthes' semiotic analysis which refers to connotative, denotative and also mythical meanings. The type of research is qualitative with descriptive methods. The research results from the film Mengjar Surga show Islamic character education values, namely optimism, trust, sincerity, religion, mutual help, courage, which can be an example of character education applied in everyday life.